2010
DOI: 10.1161/strokeaha.109.576223
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Activation in Lacunar Stroke Subtypes

Abstract: Background and Purpose-Lacunar stroke (LS) can be subtyped according to the absence (isolated lacunar infarct [ILA]) or presence of concomitant white matter lesions (WML) and/or asymptomatic lacunar infarcts. Endothelial activation is thought to play a pivotal role in the subtype with WML and/or asymptomatic lacunar infarcts. The aim of this study was to evaluate whether endothelial activation is associated with WML and/or asymptomatic lacunar infarcts in LS patients. Here, we determined levels of circulatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 36 publications
4
48
0
3
Order By: Relevance
“…Very few studies used cellular biomarkers of endothelial dysfunction. Finally, with the exception of a few studies, 52,66,74,79,84 only selective biomarkers involved in different points of the complex pathways linking together endothelial dysfunction and coagulation system/inflammation processes were analyzed. It should be underlined that the assessment of individual biomarkers cannot provide information on relative contributions by the distinct pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very few studies used cellular biomarkers of endothelial dysfunction. Finally, with the exception of a few studies, 52,66,74,79,84 only selective biomarkers involved in different points of the complex pathways linking together endothelial dysfunction and coagulation system/inflammation processes were analyzed. It should be underlined that the assessment of individual biomarkers cannot provide information on relative contributions by the distinct pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Plasminogen activator inhibitor resulted independently associated with the presence of WMH and/or lacunar infarcts and reduced fractional anisotropy on diffusion tensor imaging sequences in three studies. 71,74,79 Four studies investigated the association between D-dimer and markers of SVD. Gottesmann et al 52 found an independent association between D-dimer levels and subclinical lacunar infarcts in the Atherosclerosis Risk in Communities cohort.…”
Section: 61mentioning
confidence: 99%
“…26 Blood pressure is the major determinant of arteriosclerosis and endothelial dysfunction in patients with chronic kidney disease, 27 and endothelial dysfunction within capillaries appears to contribute to the development of CMBs. 28 Recent studies have shown that endothelial dysfunction is an important mechanism of cerebrovascular damage in patients with lacunar infarction 29 that is correlated with an increased risk of acute ischemic stroke. 30 However, the exact mechanism remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…37 An intact vascular endothelium is also required for effective autoregulation of cerebral blood flow. In a study monitoring circulating blood markers in lacunar stroke, Knottnerus et al 38 concluded that endothelial dysfunction is a significant mechanism confined to the asymptomatic but not to the symptomatic subtype.…”
Section: Factors That Increase Vulnerability To Sbimentioning
confidence: 99%
“…В исследовании по монито-рингу циркулирующих в крови маркеров лакунарного инсульта Knottnerus и соавт. [38] пришли к выводу, что дисфункция эндотелия является важным механизмом, характерным для бессимптомного, но не симптомного подтипа.…”
Section: Disclosuresunclassified